Control of crater morphology on flow path direction of Soufriere-type pyroclastic flows - Lagmay, M; Pyle, D; Dade, B; Oppenheimer, C (Blackwell Publishing Ltd, 1999)
We present a model of fountain collapse for small-scale (Soufrière-type) explosive eruptions that relates the asymmetry of a volcanic crater (e.g., the presence of crater notches) with the emplacement direction of pyroclastic flows. Analysis of two-dimensional simulations of compressible fluids emanating from asymmetric nozzles shows that under sonic to supersonic conditions, the streamline of a jet can become tilted. The inclination of the streamline increases with greater slant angle of the nozzle and with increasing exit pressure. Using the two-dimensional simulations as analogues to volcanic eruptions, we propose that pyroclastic ejecta within the inner core of an erupting jet column can become asymmetrically focused before collapsing at fountain heights of a few hundred meters above the crater exit. The ensuing pyroclastic flows associated with fountain collapse thus become directional in character with flow orientation controlled by crater geometry and eruption exit pressure. The model applies to volcanoes with vertical conduits and crater to vent geometries that act as effective sonic to supersonic jet nozzles. We propose that the 1984 eruption of Mayon volcano fits this model. In the second phase of this eruption a prominent crater notch imparted a southeastward tilt to the basal gas thrust region of the eruption column. In turn, this led to the discharge of pyroclastic flows onto the southeast flank of the volcano. Copyright 1999 by the American Geophysical Union.